Tazkiyat al-Nafs as a Solution for Reaching Humans Peace of Heart in the Modern Age - Deswita Deswita; Zaidi Hajazi; Kasmuri Selamat (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The development of the times and technology has changed the human perspective on spiritual values. This sometimes causes the presence of various flavors in the human soul. Be it peace, happiness or otherwise a sense of anxiety, discomfort, and sadness, all of which lead to the human heart, Allah gives ease to His servants in following the path of goodness and turns them away from badness and evil. Paying attention to things that can cleanse the soul and soften the heart so that it is always obedient to the shari'ah of Allah, is one of the greatest factors of goodness in this world and in the hereafter. Desire and equanimity can only be achieved if he reaches Allah. As for achieving it, a healthy and clean heart is needed, because the estuary of happiness and misery is the heart. The heart will only feel happy with sincerity to Allah. The heart will feel calm with remembrance and obey Allah. The way to achieve happiness and peace of mind is to pay attention, improve, and treat heart diseases so that they always obey His Rabb. The lucky person is the one who gets Allah's ressistance and the lowly and despicable is the one who is hindered from Allah's help. How to get happiness, serenity, help and guidance from Allah? This is what will be discussed in this study. In this study, we discuss how to achieve peace of mind through tazkiyat an-Nafs (purification of the heart or soul). Tazkiyat an-Nafs itself is an attempt to filter out the bad and dirty things from the soul, so that what comes out of the soul is the good one. Tazkiyat an-Nafs is done by following the Apostle who oversees guiding his people through the verses of Allah, through worship through the Shari'a way.┬á